Pemanfaatan Media Ajar Dalam Meningkatkan Minat Membaca Siswa Pada SD YPK Kharisma Kanaan Kota Sorong - Abu Sofyan; Faisal Eka Mahendra; Afifah Istiqomah; Fatmawati Fatmawati; Gustia Haryati; Ramin Ode; Kris Uluelang (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The Covid-19 pandemic has changed the entire order of life of the community from all fields to the field of education. As a result of the Covid-19 Pandemic that is currently attacking has resulted in learning activities that should be carried out offline or close distance learning carried out at school, turning into learning from or distance, namely at home. Learning that is carried out online is certainly not effective for the development of students. so in line with that, the Ministry of Education and Culture has created a Teaching Merdeka Campus program that provides opportunities for the younger generation to assist learning activities in schools. This Teaching Campus Program activity is carried out at SD YPK Kharisma Kanaan, Sorong City, West Papua, as the target school. This activity starts on August 03, 2021 - December 17, 2021. This activity is carried out to assist teaching and learning activities related to planning activities and assist activities in schools in the form of school accreditation, school assessment and school UAS activities, and technology adaptation. The learning method used in learning in this target school is offline, in other words, school at home using learning modules from school. In this case, the main focus is the design of learning programs related to literacy and numeracy or commonly known as reading and counting.